Fine-tuning of chromatin composition and Polycomb recruitment by two Mi2 homologues during C. elegans early embryonic development. Issue 1 (December 2016) - Käser-Pébernard, Stéphanie; Pfefferli, Catherine; Aschinger, Caroline; Wicky, Chantal
Abstract Background The nucleosome remodeling and deacetylase complex promotes cell fate decisions throughout embryonic development. Its core enzymatic subunit, the SNF2-like ATPase and Helicase Mi2, is well conserved throughout the eukaryotic kingdom and can be found in multiple and highly homologous copies in all vertebrates and some invertebrates. However, the reasons for such duplications and their implications for embryonic development are unknown. Results Here we studied the twoC. elegans Mi2 homologues, LET-418 and CHD-3, which displayed redundant activities during early embryonic development. At the transcriptional level, these two Mi2 homologues redundantly repressed the expression of a large gene population. We found that LET-418 physically accumulated at TSS-proximal regions on transcriptionally active genomic targets involved in growth and development. Moreover, LET-418 acted redundantly with CHD-3 to block H3K4me3 deposition at these genes. Our study also revealed that LET-418 was partially responsible for recruiting Polycomb to chromatin and for promoting H3K27me3 deposition. Surprisingly, CHD-3 displayed opposite activities on Polycomb, as it was capable of moderating its LET-418-dependent recruitment and restricted the amount of H3K27me3 on the studied target genes. Conclusion Although closely homologous, LET-418 and CHD-3 showed both redundant and opposite functions in modulating the chromatin environment at developmental target genes. We identified the interplay between LET-418 and CHD-3 to finely tune the levels of histone marks at developmental target genes. More than just repressors, Mi2-containing complexes appear as subtle modulators of gene expression throughout development. The study of such molecular variations in vertebrate Mi2 counterparts might provide crucial insights to our understanding of the epigenetic control of early development.